Phytochemical Study and Antibacterial and Antibiotic Modulation Activity of Punica granatum (Pomegranate) Leaves - Amine Trabelsi; Mohamed Amine El Kaibi; Aïmen Abbassi; Amira Horchani; Leila Chekir-Ghedira; Kamel Ghedira (Scientifica)
This study aimed to determine phytochemical contents, antibacterial properties, and antibiotic modulating potential of Punica granatum leaf extracts: hexane, chloroform, ethyl acetate, ethanol, and aqueous extracts as well as an extract enriched with total oligomer flavonoids (TOFs). The TOF extract contained the highest value of phenols and flavonoids. Rutin, luteolin, gallic acid, and ellagic acid were determined by HPLC analysis of this extract. The antibacterial activity was assayed by the disc diffusion method and microdilution method against Staphylococcus aureus and Escherichia coli standard ATCC strains and clinical isolates resistant strains. The TOF extract was the most active against all tested strains. The checkerboard method was used for the determination of synergy between two antibiotics (amoxicillin and cefotaxime) and P. granatum leaf extracts. The best synergistic interaction was found with TOF extract combined with amoxicillin for penicillin-resistant E. coli and penicillin-resistant S. aureus. These results can be assigned to tannins, flavonoids, and phenolic acids found in P. granatum leaf extracts. Pomegranate leaf extracts or active compounds isolated from these extracts could be used to fight the emergence and spread of resistant bacterial strains.